Giant carotid aneurysm in takayasu arteritis - Debasis Acharya; Debasish Das; Jogendra Singh; Subhas Pramanik (Journal of Indian College of Cardiology, 2022)
Takayasu arteritis is an arteritis of unknown etiology, resulting in stenosis or dilatation of the aorta and its major branches. .We report a rare case of a giant right common carotid artery aneurysm on the one side in a 29-year-old young male with refractory hypertension with severely stenotic, diffusely diseased, corkscrew appearance of the contralateral carotid artery, which has not been described in the literature so far. Our case is a unique demonstration of nature's paradox in vascular behavior in Takayasu arteritis in the right and left carotid arteries in an index patient; one having a giant aneurysm and the other one being severely stenotic, diffusely diseased with corkscrew appearance.